APLIKASI MEDIA TELENURSING PADA TATA LAKSANA DIABETES MELLITUS: SEBUAH SCOPING REVIEW - Adiputra, Andi Budiyanto Budiyanto (Universitas Islam Negeri Alauddin Makassar, 2019)
AbstractDiabetes Mellitus is currently still a global health problem. Telenursing is the use of telecommunications and information technology to provide remote nursing practice. Purpose: This scoping review aims to find out the application of telenursing models in the management of diabetes mellitus. Methods: This study is a scoping review of the literature related to telenursing media applications in DM management. The inclusion criteria were articles in the last 5 years, in English and Indonesian, full text, pure research (non-literature, and protocol studies). With the main content related to telenursing applications in DM sufferers. Results: There are ten literatures that fall into the inclusion criteria. Conclusion: There are several media that can be used in carrying out telenursing in DM management. These media are telenursing based on telephone, text messaging, virtual visits, and website based. Telenursing also has various benefits and can be an alternative of intervention methods in long-distance diabetes nursing management.